Pengaruh Media Animasi Berbasis Macromedia Flash terhadap Kemampuan Siswa Dalam Pembelajaran Fisika Hukum Archimedes di SMP/MTs - Suar Siti Hadizah; Jannnatul Aulia; Rahmawati (Lembaga Anotero Scientific Pekanbaru, 2021)
The media plays a very important role in which learning process later it will affect the understanding of concepts and results learn from students. This research aims to describe the feasibility of influence-based animation media macromedia flash on student learning abilities, based on empirical feasibility namely student response. In collecting data, the method used is to use a questionnaire and then the results are analyzed. The results of the study show that macromedia flash-based animation media against students' abilities in learning physics Archimedes Law suitable for use in learning.